Reimagining Qur’anic Pedagogy:Nadlariyah Maudu’iyah as a Methodological Innovation in Tafsir Tarbawi with Application to Child Education Themes - Abdul Hamid; Muslihudin Muslihudin; Tamsik Udin (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
AbstractThe surging scholarly interest in tafsīr mawḍūʿī (thematic exegesis) for educational (tarbawī) understanding of the Qur’an, particularly in Indonesia, currently lacks a robust methodological foundation. This study addresses this critical gap by introducing and critically establishing nadhariyyah mawḍūʿiyah (thematic theoretical framework) as a systematic hermeneutical approach tailored for educational interpretation. The research investigates its epistemological significance, proposes a definitive procedural model, and demonstrates its application to the Qur’anic theme of “Mauqifu al-Awlād wa Ṭarīqatu al-Ḥiwār Ma‘ahum” (The Qur’anic Stance Toward Children and the Method of Dialogue with Them). Employing a qualitative library-based methodology enriched by historical contextualization, Hegelian dialectics, and Popperian falsification, the study yields two primary findings. Firstly, nadhariyyah mawḍūʿiyah enables a holistic, context-sensitive interpretation that significantly enhances pedagogical relevance. Secondly, a five-stage procedural model is proposed: (i) theme identification, (ii) verse compilation, (iii) semantic validation, (iv) conceptual modeling, and (v) systematic synthesis. Applied to child education, the analysis uncovers the Qur’an’s dual portrayal of children as spiritual tests and opportunities for growth, advocating for a dialogic pedagogy grounded in affection, epistemic respect, and spiritual nurturing, which fosters moral development and emotional intimacy. This research establishes a novel methodological framework for Qur’anic hermeneutics and Islamic educational theory, offering significant implications for curriculum design, parenting discourse, and the overall rigor of tafsīr tarbawī scholarship. Keywords: Nadzariyyah Maudhu’iyah, Qur’anic hermeneutics, child education, Islamic pedagogy, dialogic parenting, Hegelian dialectics, Popperian falsification